Integração de Bacillus subtilis e cobre no manejo do cancro cítrico - Ramos, Luiz Otávio (Universidade Federal de São Carlos, 2025)
Brazilian citrus production, which leads the global orange market, is currently threatened by the accelerated spread of citrus canker, now present in 32.71% of orchard blocks and affecting more than 53 million trees. Control of the disease relies exclusively on copper-based compounds, resulting in excessive dependence and frequent applications that increase the risks of phytotoxicity, environmental contamination, and reduced sustainability of commercial orchards. This scenario exposes an urgent scientific gap: identifying alternative strategies capable of maintaining effective disease control while reducing the intensive use of copper, such as biological products formulated with Bacillus subtilis. This quantitative study evaluated the effectiveness of chemical management (copper), biological management (Bacillus subtilis), and integrated management (copper alternated with Bacillus subtilis) in three commercial sweet orange cultivars (Hamlin, Pera, and Valencia) over three consecutive seasons, conducted in commercial orchards located in the municipalities of Itatinga and Avaré, São Paulo, Brazil. The experiment followed a randomized block design with four treatments and one replication per treatment, assessing 30 plants per block. Disease severity was evaluated monthly using the diagrammatic scale proposed by Belasque Júnior et al. (2005), and epidemic progress was quantified using the Area Under the Disease Severity Progress Curve (AUDSPC). Productivity was determined by harvesting each evaluated plant, and all data were analyzed in RStudio using ANOVA and Tukey’s test at a 5% significance level. Results showed that copper was the most effective treatment, with severity ranging from 0 to 5% and AUDSPC values below 550 across all seasons and cultivars. Integrated management achieved control equivalent to biweekly copper applications while reducing the number of copper sprays by half, demonstrating promising potential to decrease dependency on this input. In contrast, Bacillus subtilis alone showed low efficacy, not differing from the untreated control in most evaluations. The cultivars displayed different susceptibility levels, with Hamlin being the most affected and Valencia the most tolerant. Rainfall had a strong influence on disease development, intensifying severity and reducing productivity in wetter years. In conclusion, copper remains the most effective strategy for controlling citrus canker; however, integrated management represents a viable alternative for reducing copper use, particularly in regions with high inoculum pressure. Bacillus subtilis alone showed limited performance, reinforcing the need for advances in sustainable alternatives to the current exclusively copper-based control approach.
Integration of Bacillus subtilis and copper in citrus canker management
Keywords: Bacillus Subtilis; Controle Biológico; Manejo Integrado; Cancro Cítrico; Biological Control; Integrated Management; Citrus Canker; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; 2. Fome Zero e Agricultura Sustentável